Research progress of biomass carbon materials as anode materials for potassium-ion batteries - Li, Xiang; Zhou, Yimiao; Deng, Bin; Li, Jiani; Xiao, Zuowei (Frontiers in Chemistry, 2023)
Biochar materials have attracted people’s attention because of their environmental friendliness, abundant resources, and the use of waste resources for reuse. As a potassium-ion anode material, biomass char materials synthesized by different methods have broad application prospects. However, due to the problems of low initial magnification and limited potassium-storage capacity, it is necessary to improve the electrochemical performance through modifications, such as atomic doping. Atomic doping is an effective way to improve battery conductivity and potassium storage. In this paper, the synthesis method of biochar as an anode material for potassium-ion batteries and the influence of atomic doping on its modification in recent years are reviewed.